(3GdOSJhQ hcjajI GdYed Hgs - (3GdTQja fYeI Hf CMeO GdRjOjs
(3ChdgG (B:s
(3bGd (B( (3GdTQja (B) (3fYeI Hf CMeO GdRjOi QMeI Gddg Ydjg GdOSJhQ fbV HSW cQI ESJNQL efgG cKjQ ef GdCYeGd GdfLhejI HCSgd WQjb , hCbQH eCNP , hgh TWQ OGFQI ebSheI s
(3BNQgG (B:s
(3cGfJ CcKQ YQV ef LgI GdTeGd Ydi NW fUa GdfgGQ Ydi NW GdeTQb hGdeZQH aEdi LgI GdeTQb hEf cGfJ Cbd WhdkG aEdi LgI GdeZQH , hdGjecf Cf jJSGhi GdWhdGf hGdYQVGf CHOkG hGddg CYde Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B7s
(3fSNI NRGFfjIs
(3cJHJ Hbde eVHhWs
(3HBNQgG Jedc SfI (B817(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdadcs